Giant omental cyst: Laparoscopically managed (Indian Journal of Case Reports, 2020)
Omental and mesenteric cysts are rare intra-abdominal pathology in children. Children with these pathologies mostly present with abdominal distension with or without palpable abdominal mass. It can mimic ascites, gross hydronephrosis, abdominal tuberculosis, etc. The preferred treatment of choice is complete excision. We present a case of a 6-year-boy child with gradually increasing abdominal distension with suspicion of the mesenteric cyst. The laparoscopic intervention was done, which led to the correct diagnosis, that is, giant omental cyst. Histopathology was suggestive of cystic lymphangioma.